Stability of a Class of Nonlinear Neutral Stochastic Differential Equations with Variable Time Delays - Wu Meng; Huang Nanjing; Zhao Changwen (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2012)
In this paper, we study the mean square asymptotic stability of a class of generalized nonlinear neutral stochastic differential equations with variable time delays by using fixed point theory. An asymptotic mean square stability theorem with a necessary and sufficient condition is proved which improves and generalizes some well-known results. Finally, two examples are given to illustrate our results.